Whole-genome analysis of Alu repeat elements reveals complex evolutionary history - Price, Alkes L.; Eskin, Eleazar; Pevzner, Pavel A.

(untitled) (Genome Research, 2004)
Alu repeats are the most abundant family of repeats in the human genome, with over 1 million copies comprising 10% of the genome. They have been implicated in human genetic disease and in the enrichment of gene-rich segmental duplications in the human genome, and they form a rich fossil record of primate and human history. Alu repeat elements are believed to have arisen from the replication of a small number of source elements, whose evolution over time gives rise to the 31 Alu subfamilies currently reported in Repbase Update. We apply a novel method to identify and statistically validate 213 Alu subfamilies. We build an evolutionary tree of these subfamilies and conclude that the history of Alu evolution is more complex than previous studies had indicated.